Alteration of physicochemical properties of tap water passing through different intensities of magnetic field - Jawad Saba I.; Karkush Mahdi; Kaliakin Victor N. (Journal of the Mechanical Behavior of Materials, 2023)
This study reports the effect of the magnetization process on the chemical and electrical properties of tap water (TW). Also, a step in the direction of gaining a better understanding of the influence of magnetizing technique on the physicochemical properties of water exposed to several intensities of magnetic field (MF). The TW sample used in this study passed through four intensities of the MF (2,000, 4,000, 6,000, and 8,000 G) under the same conditions of temperature and pressure. Magnetized water was tested and evaluated for physical and chemical qualities after being cycled through a magnetization device for 6 h. Following the increase in the intensities of the MF, the alteration in water properties has been depicted. The results showed increase in the pH value, electrical conductivity, and some of the chemical properties. The optimum change in the properties of water were obtained when the intensity of MF reached 8,000 G. However, to assess the obtained modification of water quality from the magnetization process, the results are compared with the guideline standards of the World Health Organization. To reduce the treatment costs and increase the long-term viability of the process, the study findings suggested a strategy of water magnetization as an effective treatment technology with reduction in energy and material usage (green technology).